Paediatric intubation in Australasian emergency departments: A report from the ANZEDAR. (3rd December 2019) - Ghedina, Nicole; Alkhouri, Hatem; Badge, Helen; Fogg, Toby; McCarthy, Sally
Abstract: Objectives: To describe the epidemiology, clinical practice and outcomes of paediatric ED intubation in Australia and New Zealand. Method: Prospectively collected airway management audit data from 43 EDs in Australia and New Zealand that was submitted to the Australia and New Zealand Emergency Department Airway Registry between 2010 and 2015. Results: Paediatric cases accounted for 4.94% (270/5463) of cases (median age = 3, interquartile range [IQR] = 2–9). A median of 5 (IQR = 2–9) intubations were reported per department per year. Most intubations were performed for medical indications (72.2%), including seizure (25.2%) and respiratory failure (15.2%). Patients were physiologically compromised prior to intubation with 69.5% comatose, 50.9% outside of the normal age‐adjusted range for respiratory rate, 15.9% hypoxic and 12.6% hypotensive. Complication rate was 33.3% and desaturation was the most common (18.5%). The ED mortality rate was 3.8%. First pass success (FPS) was 80% (95% CI 75.2–84.8). Infants less than 1 year of age had lower FPS, higher rates of difficult laryngoscopy and higher rates of desaturation than other age groups. Conclusion: Paediatric intubation in Australasian EDs is rare from a departmental and individual provider viewpoint. Success rates are similar to contemporary international registries. Complications are common and ongoing collaborative multicentre audit with resultant quality improvement is desirable to facilitate improved success and reduced complications.